1988
DOI: 10.1002/cne.902730309
|View full text |Cite
|
Sign up to set email alerts
|

Putative cholinergic projections from the nucleus isthmi and the nucleus reticularis mesencephali to the optic tectum in the goldfish (Carassius auratus)

Abstract: The nucleus isthmi of fish and amphibians has reciprocal connections with the optic tectum, and biochemical studies suggested that it may provide a major cholinergic input to the tectum. In goldfish, we have combined immunohistochemical staining for choline acetyltransferase with retrograde labeling of nucleus isthmi neurons after tectal injections of horseradish peroxidase. Seven fish received tectal horseradish peroxidase injections, and brain tissue from these animals was subsequently processed for the simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
61
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 44 publications
11
61
0
Order By: Relevance
“…A common feature of the isthmic nucleus in nonmammalian vertebrates is the cholinergic nature of its cells [Brauth et al, 1985;Desan et al, 1987;Ekström, 1987;Brantley and Bass, 1988;Zottoli et al, 1988;Sorenson et al, 1989;Bagnoli et al, 1992;Medina and Smeets, 1992;Medina et al, 1993;Molist et al, 1993;Powers and Reiner, 1993;Medina and Reiner, 1994;González et al, 2002]. Recently, similar cholinergic nuclei have been suggested in elasmobranch chondrostean and teleost fishes [Adrio et al, 2000;Anadón et al, 2000;Pérez et al, 2000], as well as in lampreys [Pombal et al, 2001; see also Rodríguez-Moldes et al, 2002].…”
Section: Rhombencephalic Projectionsmentioning
confidence: 84%
See 1 more Smart Citation
“…A common feature of the isthmic nucleus in nonmammalian vertebrates is the cholinergic nature of its cells [Brauth et al, 1985;Desan et al, 1987;Ekström, 1987;Brantley and Bass, 1988;Zottoli et al, 1988;Sorenson et al, 1989;Bagnoli et al, 1992;Medina and Smeets, 1992;Medina et al, 1993;Molist et al, 1993;Powers and Reiner, 1993;Medina and Reiner, 1994;González et al, 2002]. Recently, similar cholinergic nuclei have been suggested in elasmobranch chondrostean and teleost fishes [Adrio et al, 2000;Anadón et al, 2000;Pérez et al, 2000], as well as in lampreys [Pombal et al, 2001; see also Rodríguez-Moldes et al, 2002].…”
Section: Rhombencephalic Projectionsmentioning
confidence: 84%
“…A direct tectal connection from the isthmus has been found in all vertebrates studied so far [Nieuwenhuys et al, 1998]. In most teleosts this connection is only ipsilateral [Ebbesson and Vanegas, 1976;Grover and Sharma, 1981;Luiten, 1981;Sakamoto et al, 1981;Ito et al, 1982b;Northcutt, 1982;Vanegas and Ito, 1983;Zottoli et al, 1988;Yamamoto et al, 1999], as well as in the leopard frog [Wilczynski and Northcutt, 1977]; however, bilateral connections were found in other fish [Dunn-Meynell and Sharma, 1984;Sas and Maler, 1986] and amphibian species [Glasser and Ingle, 1978;Grobstein et al, 1978;Gruberg and Udin, 1978;Gruberg and Lettvin, 1980;Grobstein and Comer, 1983;Desan et al, 1987;Rettig, 1988;Marín et al, 1999].…”
Section: Rhombencephalic Projectionsmentioning
confidence: 99%
“…Since ChAT-positive afferents from the nucleus isthmi and possibly other nuclei (e.g. nucleus reticu laris mesencephali [Zottoli et al, 1985]) project to the tectum, the extent and pat terns of type XIV arborization may be partially obscured by the presence of these fibers. However, some individual neurons stained in near isolation of other ChATpositive cell bodies and neurites.…”
Section: Cha T Immunohistochemistrymentioning
confidence: 99%
“…These results are discussed in the context of the organization of intrinsic and extrin sic sources of cholinergic innervation of the tectum. Preliminary accounts of this research have been reported previously [Zottoli et al, 1985.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation